Exploring blended learning tools to transform a laboratory course unit in engineering: Challenges, setbacks and rewards - Pereira, Maria Olívia (2021)
To boost students engagement on learning outcomes, promote active peer learning, and adopt more dynamic teaching practices, a module of a laboratory course unit (TPL) in engineering was reformulated exploring blended learning. This reformulation was even more challenging than initially anticipated as it was implemented during the Covid-19 pandemic. As TPL learning practises are based on the operation of laboratory modules mimicking heat and mass transfer phenomena, asynchronous and on-line synchronous learning classes and face-to-face laboratory classes were outlined. To promote the asynchronous learning, a full script of TPL and pitch and longer videos presenting, respectively, each work and its practical operation process were formerly prepared and available online. Students were required to work in group to define the variables and conditions to be evaluated in each laboratory module, organize and plan the experimental activities, create data recording documents, and later present and argue their options in virtual synchronous classes. In the face-to-face classes, different activities were performed in a rotating system, scheduled and tuned in the online classes. It was also aimed in-situ promoting peer discussion of the data and reports elaboration, goals not attained due to the pandemic restrictions, as only two students of each group were present in each hands-on class and in sequential times. TPL reformulation was a tough and time-consuming task since 73 students were enrolled, divided into 3 shifts, each one with 5 groups of five students. Students individual learning evolution was inferred through online quizzes that were periodically made available. A final inquiry, launched to obtain students` opinion about this transformation endeavour highlighted the script, videos, and the prompt teachers feedback on the reports as the most fruitful and important aspects for students engagement and guide their learning pathway. The rationale behind this paper was to disclose this transformation experience and share information and strategies that can be used in the teaching/learning of laboratory classes. © 2021 University of Minho. All rights reserved.